EPC Minutes 2004-04-01 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Agenda – Approved. Minutes – Approved. Consent Calendar: Faculty Eligible for Emeritus Status: Joaquin Lopez, Athletics and Michael Lyle, Computer Science; Revision to Pre-Business – Approved. President Report. Provost Report. Vice Chair Report. Associated Students Report. Statewide Senator Report. Staff Representative Report. Discussion: Expectation of committee members across faculty governance. Vice President for Student Affairs Report. APARC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Good of the Order.